Storytelling in literary and language teachingof German - KUZMINYKH, KSENIA (Glottodidactica, 2017)
The article starts with a discussion of the essential theories of storytelling, reading and writing, and focuses on the concept of reading-to-write. It discusses the use and the abuse of classical schema of storytelling – “the mouse”. In the last step, using fragments of different children’s books, the article develops an integrative literary and language teaching model for school lessons of German in a way which stimulates a highly functional receptive and productive handling of language semantics and performance.